Hindu-Buddhist Archaeological Traces in Temanggung Regency as Sources of Local History and Reflections of Multicultural Values - Winda Prastyaning Adhy; Zukhrufa Ken Satya Dien; Veri Setiawan (Local History & Heritage, 2026)
Temanggung Regency represents one of the significant regions in the historical development of the Ancient Mataram Kingdom, as evidenced by the abundance of Hindu-Buddhist archaeological remains found throughout the area. This study aims to identify the archaeological potential of Hindu-Buddhist heritage in Temanggung Regency as a source of local history and to examine the multicultural values reflected in these cultural remains. The research employed a qualitative method, drawing on historical and archaeological approaches. Data were collected through literature reviews, field observations, documentation, and interviews with informants knowledgeable about local cultural heritage. Data analysis involved data reduction, verification, historical interpretation, and the construction of local historical narratives. The findings reveal that Temanggung Regency possesses a rich archaeological legacy, including at least 32 inscriptions, the Liyangan Site, temples, statues, yoni, lingga, and various other artifacts associated with the Ancient Mataram Kingdom. These remains provide valuable information concerning the political, social, economic, religious, and cultural life of Hindu-Buddhist communities in the past. The study argues that, beyond functioning as important sources of local history, these archaeological traces embody multicultural values, such as tolerance, cultural acculturation, openness to external influences, and respect for diversity, which have long characterized the historical development of local society.